2003
DOI: 10.1023/b:phar.0000006526.55922.8d
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and economic impact of a secondary heart disease prevention clinic jointly implemented by a practice nurse and pharmacist

Abstract: A secondary heart disease clinic can benefit patients by optimising drug and lifestyle therapy. While the inclusion of a pharmacist confers clinical and economic benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…[295][296][297][298][299] All of the studies looked at clinics where practice nurses monitored lipid levels, blood pressure, medication use and other risk factors such as diet, exercise and smoking. Three studies [300][301][302] looked at the effect of nurse-led interventions in primary care on patient compliance with drug regimens for high blood pressure.…”
Section: Health Improvement Activities Undertaken In General Practicementioning
confidence: 99%
See 1 more Smart Citation
“…[295][296][297][298][299] All of the studies looked at clinics where practice nurses monitored lipid levels, blood pressure, medication use and other risk factors such as diet, exercise and smoking. Three studies [300][301][302] looked at the effect of nurse-led interventions in primary care on patient compliance with drug regimens for high blood pressure.…”
Section: Health Improvement Activities Undertaken In General Practicementioning
confidence: 99%
“…However, what small improvements there were may be misleading, as they relied on patients self-reporting. [295][296][297][298][299] In a study that looked at the effect of nurse-led interventions in primary care on patient compliance with drug regimens for high blood pressure, Schroeder et al 300 found that there was no effect on patient compliance, while another study 302 found that there was some improvement. Bane et al 301 concluded that compliance was more likely if patients felt that they had been 'listened to' by their GP in the initial consultation.…”
Section: Effectiveness Of Health Improvement Activities Undertaken Inmentioning
confidence: 99%
“…describes a Pharmacist-Led Cardiac Risk Reduction Clinic (CRCC) in the USA, where risk reduction in terms of Framingham risk score for CHD was reduced in patients participating in the CRCC [11,12]. Reilly and Cavanagh describe a successful pharmacist-nurse-run clinic for patients with cardiovascular disease in terms of optimizing drug and lifestyle therapy [13]. Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…Reductions in all-cause mortality associated with CVD in the patients followed by the service, and high satisfaction with the CCCS, was reported by both patients and physicians. Similar positive outcomes were demonstrated in other team care approaches [17,18,19]. As such, adequately preparing health care students (HCSs) for the provision of interprofessional CVDRAM services may be a valuable strategy not only to promote the adoption and the full integration of CVD risk assessment into primary care services but, most importantly, to improve the cardiovascular health of the public.…”
Section: Introductionmentioning
confidence: 76%